Effect of Biological Pretreatment of Water Hyacinth on Enzymatic Hydrolysis for Bioethanol Production - Syamsiah1, S.; Sulistyo1, H.; Hidayat1, M. (Asian Journal of Chemistry, 2014)
The key to success in increasing the glucose yield lies in the need to optimize the pretreatment process. The expectation is that lignocellulosic materials will be more easily hydrolyzed by the cellulase enzymes and produce a high yield of glucose. To improve the digestibility of water hyacinth in the enzymatic hydrolysis process and improve glucose production release, it is necessary to optimize of a pretreatment process. We evaluated the effects of varying biological pretreatment process conditions such as initial moisture content (IMC), material size, the addition of molasses and Co-factor Mn2+ for lignin degradation and the glucose production The results showed that choosing a 70 % IMC can provide increased yields of glucose reached 16.87 %. Selecting material size provides a glucose yield enhancement of 20.02 %. To prevent the degradation of cellulose in the pretreatment process the addition of molasses at a concentration of 2 % gave encouraging results, with the glucose yield reaching 43.91 %. Further, addition of co-factor Mn2+ using a concentration of 0.5 % significantly increased the yield of glucose, which reached 66.67 % during 16 days of incubation.